Taxonomy of the Caribbean sponge Dragmacidon reticulatum (Ridley & Dendy, 1886) (Porifera, Demospongiae, Axinellida), with the description of a new species - Zea, Sven; Pulido, Alejandra (Zootaxa, 2016)
Although there is a long history of taxonomic investigation in Caribbean sponges, there are still many undescribed species. Furthermore, field observations and corroborating morphological analyses are revealing that what was believed to be single, somewhat variable species, may consist of two or more species, often easier to distinguish once well characterized. This is the case for Dragmacidon reticulatum (Ridley & Dendy, 1886) (Porifera, Demospongiae, Axinellida, Axinellidae), a rather well-known sponge, with an ample distribution and presence in rocky and reef environments of the tropical and subtropical Western Atlantic, with local records in the majority of the countries of the area, from Bermuda to Brazil. Field observations and a detailed review of material from different areas, including some type specimens, led us to the distinction of two different species in terms of external morphology, size of spicules, and skeletal architecture. The distinction was confirmed in the Bahamas and Santa Marta, Colombia, where the two species coexist. One of the species is Dragmacidon reticulatum sensu stricto, but for the other there is need to erect a new name, for which we propose Dragmacidon alvarezae n. sp. The purpose of the present work is to describe, illustrate and compare these two species.